2011
DOI: 10.4103/1119-3077.91750
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of colorectal carcinoma among Nigerians: A 30-year review

Abstract: Colorectal carcinoma is no longer a rare disease in Nigeria. The surge in the incidence reported in the last 5 years in this center calls for a pragmatic action in its control, with emphasize on colonoscopic screening for those with family history, and possibly making digital rectal examination a mandatory aspect of clinical examination, because most colorectal carcinomas are within the reach of examining finger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 17 publications
5
18
0
Order By: Relevance
“…Similar to other authors, we found a higher male-tofemale ratio in our West African population. [7][8]10 This male preponderance may be explained by higher suspected rates of male tobacco use and abdominal obesity 5,8 or may reflect a selection bias that results from well-documented gender inequity in access to healthcare. 12 The possibility of different tumor biology is clearest when considering the metastatic pattern observed in the two centers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar to other authors, we found a higher male-tofemale ratio in our West African population. [7][8]10 This male preponderance may be explained by higher suspected rates of male tobacco use and abdominal obesity 5,8 or may reflect a selection bias that results from well-documented gender inequity in access to healthcare. 12 The possibility of different tumor biology is clearest when considering the metastatic pattern observed in the two centers.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] In Nigeria, Ibrahim et al found that 40% of all CRC cases observed in a 30-year period occurred in the final five years of the study (2004)(2005)(2006)(2007)(2008). Meanwhile the surgical biopsy registry at Lagos University Teaching Hospital has identified CRC as the third most commonly diagnosed malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Liver cancer has risk factors ranging from infection with Hepatitis B or C viruses to alcohol use and food Colorectal cancer is also no longer a rare disease in Nigeria as evidenced in a review which showed that out of 241 cases in the last 30 years, 93 cases were seen in the last 5 years (Ibrahim et al, 2011).…”
Section: Introductionmentioning
confidence: 99%